Population-associated differences between the phase variable LPS biosynthetic genes of Helicobacter pylori - Salaün, L; Saunders, N (BioMed Central, 2006)
Background: Population structures are normally determined using genes under minimal functional selection. In this study we have assessed genes that are not always essential, show differences in alleles between strains, and are involved in the directly host-selectable phenotype of LPS biosynthesis. Results: Eight complete LPS biosynthesis genes, seven of which are associated with phase variation in some or all strains of Helicobacter pylori, have been sequenced and their divergence analyzed. The differences observed indicate that recombination within these genes largely reflects exchange between strains within the population lineages previously determined on the basis of MLST using housekeeping genes. This indicates that the differences that are used for MLST are likely to broadly associate with genes under functional selection, and differences in strain behaviour. However, instances of exchange between the subpopulations were identified, including the hpAfrica2 subpopulation. Further, there were other differences in gene complements and the chromosomal location of genes indicative of greater diversity within the population than is revealed by the available genome sequences and comparative genome hybridization studies. Conclusion: These results indicate that the described population structure based upon MLST is broadly a good basis for studying the biology of H. pylori, but that individual alleles may not follow these associations. As a consequence, when working in unsequenced strains, it is necessary to carefully check the presence, sequence, and distribution of any individual gene of interest.